MONITORING OF THE FLU SYNFROME IN FORTALEZA USING QGIS - Hil´ario Magalhães , Poliana; Marinho Campelo, Cassio (Cadernos ESP, 2025)
Objective: To evaluate the spatial and temporal distribution of flu-like illness cases in the city of Fortaleza. Methods: This is a descriptive, exploratory and analytical epidemiological study, with a quantitative approach, carried out using a spatial analysis of flu syndrome data from health centres in Fortaleza - CE, between 2021 and 2023. Results: 5938 ILI records were analysed. During the period studied, the annual target was not reached. The viral identification panel showed an increase in cases of unspecified GS, even with the incidence of SARS-Cov-2 circulation and an increase in COVID-19 cases. Females were prevalent in the economically active population. Georeferencing facilitated the monitoring of the spread of SARS, as well as health care for the areas of greatest viral circulation. Conclusion: Monitoring flu-like illness facilitated the identification of viral spread and the determination of priority health areas.
Keywords: Sentinel surveillance; Geographic mapping